Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s00705-011-1060-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of env and gag gene fragments of bovine leukemia viruses (BLVs) from cattle in Turkey

Abstract: The aim of this work was to investigate the molecular characteristics of bovine leukemia viruses (BLVs) in Turkey. The variability of env and gag fragments of BLVs was examined using DNA from blood samples obtained for sequence analysis of BLVs in four cattle herds from three different geographical areas in Turkey. The env gene sequences were highly similar to those of Brasilian, Argentine, and Japanese BLV strains, while gag genes from Turkish BLV isolates showed greatest similarity to those of Iranian isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(33 reference statements)
1
5
1
Order By: Relevance
“…Genetic distance analysis of 14 sequences representing BLV isolated in Moldova and 35 sequences representing each of the known genotypes (G1-G10) revealed 95.3% to 99.8% sequence identity at the nucleotide level. Thus, our data confirmed the high degree of conservation of the gp51 env gene sequence among geographically different strains, as has been reported previously for many BLV isolates [7, 8, 10, 2730]. …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Genetic distance analysis of 14 sequences representing BLV isolated in Moldova and 35 sequences representing each of the known genotypes (G1-G10) revealed 95.3% to 99.8% sequence identity at the nucleotide level. Thus, our data confirmed the high degree of conservation of the gp51 env gene sequence among geographically different strains, as has been reported previously for many BLV isolates [7, 8, 10, 2730]. …”
Section: Discussionsupporting
confidence: 92%
“…Since the dissemination of BLV infection is associated mainly with introduction of infected cattle into a herd, we speculate that animal trade that took place between countries belonging to CMEA (Council for Mutual Economic Assistance) played a critical role in modulation of the topology of the phylogenetic tree. The role of animal trade in BLV diversification has been emphasized in some studies [30, 32, 38]. Although we demonstrated that most Moldovan strains were of genotype G7, two strains clustered within G4, in close proximity to isolates from France, Mongolia and Belgium.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…The in vivo mutation rate of the env gene, still considered very low, is approximately 0.009 % nucleotide changes per year [17]. It has been demonstrated that this gene contains several restriction sites that allow the classification of BLV strains into several different genotypes [15,18]. Furthermore, it contains highly conserved regions that are involved in the interaction between target cells and the virus [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The infectivity and/or pathogenicity of BLV may be affected by alterations in the env gene, which is considered as one of the most variable regions of the BLV genome (5). The classification of BLV strains into several different genotypes depends on the several restriction sites that this gene contains (6). In addition, it has conserved regions that are involved in the interaction between target cells and the virus.…”
Section: Introductionmentioning
confidence: 99%